Axial compression behaviour of reinforced wallettes fabricated using wood-wool cement panel - Md. Noh, M. S.; Kamarudin, A. F.; Mokhatar, S. N.; Jaudin, A. R.; Ahmad, Z.; Ibrahim, A.; Muhamad, A. A. (2018)
Wood-wool cement composite panel (WWCP) is one of wood based composite material that produced in a stable panel form and suitable to be used as building wall system to replace non-ecofriendly material such as brick and other masonry element. Heavy construction material such as brick requires more manpower and consume a lot of time to build the wall panel. WWCP is a lightweight material with a density range from 300 kg/m3 to 500 kg/m3 and also capable to support an imposed load from the building. This study reported on the axial compression behaviour of prefabricated reinforced wallettes constructed with wood-wool cement panel. A total of six specimens were fabricated using two layers of cross laminated WWCP bonded with normal mortar paste (Portland cement) at a mix ratio of 1:3 (cement : sand). As part of lifting mechanism, the wallettes were equipped with three steel reinforcement (T12) that embedded inside the core of wallettes. Three replicates of wallettes specimens with dimension 600 mm width and 600 mm length were fabricated without surface plaster and with 16 mm thickness of surface plaster. The wallettes were tested under axial compression load after 28 days of fabrication until failure.The result indicated that, the application of surface plaster significantly increases the loading capacity about 35 % and different orientation of the panels improve the bonding strength of the wall.